2021
DOI: 10.1242/jeb.243000
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome-dependent magnetoreception in a heteropteran insect continues even after 24 h in darkness

Abstract: Sensitivity to magnetic fields is dependent on the intensity and color of light in several animal species. The of light-dependent magnetoreception working model points to Cryptochrome (Cry) as a protein able to cooperate with its cofactor flavin, which possibly becomes a magnetically susceptible pair upon excitation by light. What type of Cry is involved as well as what pair of magnetosensitive radicals are responsible is still elusive. Therefore, we developed a conditioning assay for the firebug (the firebug)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…However, the Luc-CT response is potentiated by increasing the cytosolic availability of FAD, a common biological redox cofactor, confirming that redox reactions are at the core of magnetosensitivity 43 . The finding that alternative RPs can transduce physiological MF effects also suggests that other, nonphotochemical RPs, may contribute to magnetoreception, which is consistent with a growing list of examples reporting RP mediated magnetoreception in darkness 29,[44][45][46] . The synergistic interaction between Luc-CT and free FAD suggests the former facilitates formation of a complex that enables the transduction of a magnetic signal by the latter.…”
Section: Discussionsupporting
confidence: 81%
“…However, the Luc-CT response is potentiated by increasing the cytosolic availability of FAD, a common biological redox cofactor, confirming that redox reactions are at the core of magnetosensitivity 43 . The finding that alternative RPs can transduce physiological MF effects also suggests that other, nonphotochemical RPs, may contribute to magnetoreception, which is consistent with a growing list of examples reporting RP mediated magnetoreception in darkness 29,[44][45][46] . The synergistic interaction between Luc-CT and free FAD suggests the former facilitates formation of a complex that enables the transduction of a magnetic signal by the latter.…”
Section: Discussionsupporting
confidence: 81%
“…A lot of evidence suggests that the superoxide radical is the most plausible radical under such circumstances 429,430,[434][435][436][437][438] . This is also consistent with animal magnetoreception in dark [439][440][441] , as it was suggested that during the backreaction, a radical pair is formed between flavin and an O 2 and that the radical pair reaction responds significantly to reorientation in the geomagnetic field 433,434,[442][443][444] . Such a radical pair could be generated without further absorption of light in the form of [FADH ...O -2 ].…”
Section: Cryptochrome-based Radical Pairssupporting
confidence: 85%
“…The evolution of CRY might be shaped by its additional roles, including its involvement in seasonality, as was shown in the bean bug ( Ikeno, Katagiri, et al 2011 ; Ikeno, Numata, et al 2011 ) and in the linden bug Pyrrhocoris apterus ( Urbanova et al 2016 ). CRY proteins seem to participate in magnetoreception as was reported for CRY-d in the monarch butterflies ( Wan et al 2021 ) and Drosophila ( Yoshii et al 2009 ; Fedele et al 2014 ), and for CRY-m in cockroaches ( Bazalova et al 2016 ), P. apterus ( Netusil et al 2021 ), and birds ( Xu et al 2021 ).…”
Section: Introductionmentioning
confidence: 59%